Occurrence of the hemoparasite Cyrilia spp. in the Amazonian stingray Potamotrygon wallacei - ANA CLARA N. ALVES; LARISSA D. FONSECA; RAYANA M. PAIXÃO; ADRIANO T. OLIVEIRA (Anais da Academia Brasileira de Ciências)
Abstract Freshwater stingrays play a crucial ecological role in the Amazon; however, studies on their parasitic fauna still need to be made available. This study aimed to investigate the occurrence of hemoparasites, specifically Cyrilia spp., in specimens of Potamotrygon wallacei from the Lower Rio Negro, Brazil. The research was conducted through nighttime fishing at Praia do Açutuba and the Tupé Sustainable Development Reserve. Blood samples were collected by puncturing branchial vessels, and smears were stained and analyzed under a microscope for parasitemia quantification. The results showed that specimens from Açutuba did not present significant parasites, except for one individual, which exhibited a possible macrogamont. In contrast, all specimens from Tupé displayed various parasitic stages, with parasitemia levels ranging from 0.2% to 1.3%. Morphological analysis identified predominantly intracellular stages such as trophozoites, pre-gamonts, macrogamonts, and microgamonts. It was noted that the observed stages were more similar to those characteristic of the genus Cyrilia spp. than to any other haemogregarines in fish. The study concluded that environmental and site-specific factors, such as habitat type, may influence parasitic distribution, with igapó areas favoring higher parasitic activity than beach areas.